The Function of Astrocyte Mediated Extracellular Vesicles in Central Nervous System Diseases - Gharbi, Tahereh; Zhang, Zhijun; Yang, Guo-Yuan (Frontiers in Cell and Developmental Biology, 2020)
Astrocyte activation plays an important role during disease-induced inflammatory response in the brain. Increased evidence demonstrated that the functions of astrocyte provided is largely through exosome communication. Exosomes in the brain could be released from bone marrow (BM)-derived stem cells, neuro stem cells, mesenchymal stem cells, and etc. We summarized that exosome release and transport signaling to the target cells, and then produce function. Furthermore, we discussed pathological interactions between astrocytes and other brain cells, which related to brain diseases such as stroke, Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis disease, multiple sclerosis, psychiatric, traumatic brain injury, and etc. We provide comprehensive and valuable information as well as the latest involvement of exosomes during brain disease, which is beneficial for basic researchers and clinical physicians.